Phylogeography of Amygdalus mongolica in relation to Quaternary climatic aridification and oscillations in northwestern China - Zhang,Lin; Sun,Fangfang; Ma,Songmei; Wang,Chuncheng; Wei,Bo; Zhang,Yunling (PeerJ, 2022)
Quaternary period geological events and climatic oscillations significantly affect the geographic structure and genetic diversity of species distribution in arid northwestern China. Amygdalus mongolica is a relict and endangered shrub that occurs primarily in arid areas of northwestern China. Based on variation patterns present at three cpDNA regions (psbK-psbI, trnL-trnF and trnV) and in one nDNA sequence (ITS1-ITS4) in 174 individuals representing 15 populations, the spatial genetic structure and demographic history of A. mongolica was examined across its entire geographic range. The 17 different haplotypes and 10 ribotypes showed two lineages, distributed across the Western (Mazong Mountains, Hexi Corridor, and Alxa Left Banner) and Eastern regions (Urad Houqi, Yinshan Mountains, Urad Zhongqi, and Daqing Mountains) according to the median-joining network and the BI (Bayesian inference) and ML (Maximum likelihood) trees. AMOVA analysis demonstrated that over 65% of the observed genetic variation was related to this lineage split. The expansions of the Ulanbuhe and Tengger deserts and the eastward extension of the Yinshan Mountains since the Quaternary period likely interrupted gene flow and triggered the observed divergence in the two allopatric regions; arid landscape fragmentation accompanied by local environmental heterogeneity further increased local adaptive differentiation between the Western and Eastern groups. Based on the evidence from phylogeographical patterns and the distribution of genetic variation, A. mongolica distributed in the eastern and western regions are speculated to have experienced eastward migration along the southern slopes of the Lang Mountains and westward migration along the margins of the Ulanbuhe and Tengger deserts to the Hexi Corridor, respectively. For setting a conservation management plan, it is recommended that the south slopes of the Lang Mountains and northern Helan Mountains be identified as the two primary conservation areas, as they have high genetic variation and habitats that are more suitable.
Keywords: Amygdalus mongolica; Allopatric differentiation; Postglacial expansion; Genetic conservation; Northwestern China